Treating Chronic Tendinopathy: Physical Therapy, Surgery and Other Form of Therapy - Łukawski, Artur; Szałajska, Julia; Wojtach, Klaudia; Czyżewski, Filip; Wiak, Iga; Banyś, Filip; Bochen, Konrad; Jasiński, Filip; Dziegciarczyk, Anna; Górska, Weronika (Quality in Sport, 2024)
Introduction: The term "tendinopathy" refers to pathological changes in tendons. The previously used term "tendonitis" does not fully capture the nature of the condition, as inflammatory changes, when present, are secondary to degenerative damage. Tendinopathies are quite common in the general population. Aim: The aim of this review is to characterize various types of tendinopathies, with a focus on both conservative and surgical treatment methods, in order to organize available information that may be helpful for clinicians in their practice. State of Knowledge: Chronic tendinopathies develop as a result of multiple factors. The most significant include improper exercise techniques, excessive strain, and musculoskeletal system abnormalities. Summary (Conclusions): The approach to tendinopathy treatment should vary depending on the patient’s clinical condition and provoking factors. Physiotherapy plays the most important role, along with supportive methods such as analgesic pharmacotherapy and cryotherapy. Surgical intervention may be necessary in cases where conservative treatment fails.